Single‐Walled Carbon Nanotubes Shock‐Compressed to 0.5 Mbar (Phys. Status Solidi B 11/2017). Issue 11 (16th November 2017) - Botella, Pablo; Devaux, Xavier; Dossot, Manuel; Garashchenko, Viktor; Beltzung, Jean Charles; Soldatov, Alexander V.; Ananev, Sergey
Abstract : Single‐walled carbon nanotubes (SWCNTs) have been dynamically (shock) compressed to 0.5 Mbar, above the limit of their structural integrity. Two distinct types of material are identified by high‐resolution transmission electron microscopy (HRTEM) and multi‐wavelength Raman spectroscopy in the sample recovered after shock: multi‐layer graphene (MLG) and a two‐phase material composed of nano‐clustered graphene and amorphous carbon whereas no diamond‐like carbon or carbon nano‐onions are found. Peak decomposition of the Raman spectra was used to estimate the coherent scatterers (clusters) size in MLG at 36 nm from the D‐ to G‐band intensity ratio dependence on the photon excitation energy. Botella et al. (article no.1700315 ) propose the peak fitting model for decomposition of the Raman spectra of highly disordered carbon material containing graphene nano‐clusters and stress the importance of accounting for heptagonal‐ and pentagonal‐ring defects in graphene layers for the analysis of such spectra. The cover image shows HRTEM images and the correspondent Raman spectra of the two types of material along with peak decomposition of the two‐phase material with the peaks assigned to heptagons (a) and pentagons (b). Particulars of the SWCNTs transformation to other structural forms of carbon at high pressure/temperature are discussed.